KEBIJAKAN DONALD TRUMP DALAM MERESPONS NUKLIR KOREA UTARA PERIODE 2017-2019 - Yolanda Putri Yonika (2021)
This research discusses about Donald Trump's policy analysis call nuclear North Korea. The United States and North Korea have bad relationship and nuclear disputes. US Foreign Policy has responded to North Korea's Nuclear Program in the form of imposing economic sanctions on North Korea from time to time until the Trump administration. However, giving sanctions is an ineffective method. This is because North Korea continues to develop its nuclear program from time to time until the Kim Jong-Un administration. Therefore, during the Trump administration, the United States persued another way, namely the denuclearization strategy program. The denuclearization strategy program is considered to be an effective strategy in suppressing North Korea's nuclear program. To support this research, the authors use several theories and concepts to support the author's analysis. The theories and concepts in this study include: Foreign Policy, National Interest, Offensive Realism, and Detterence. The research method used by the author is qualitative method with a descriptive approach. The author conducted a literature study, namely collecting data from books, articles, journals and internet. The final-result of this research is the significance of Donald Trump's policy in encouraging and suppressing North Korea's nuclear program. Denuclearization program became less effective because the negotiation process was not running smoothly and found no result. However,other policies in an effort to support denuclearization have become preventive measures in preparatiom for facing the worst risk from the threat of nuclear conflict. Keywords: denuclearization, national interest, foreign policy, the United Statesn North Korea, Kim Jog Un, Donald trump